ANALYSIS OF STUDENT ERRORS IN SOLVING TRIGONOMETRY PROBLEMS BASED ON THE NEWMAN PROCEDURE - Nur Isna Fauzi; Laela Sagita; Setiyani; Bintang Wicaksono (KALAMATIKA Jurnal Pendidikan Matematika, 2022)
This study was motivated by student errors in trigonometry. This study aimed to describe the types of student errors in solving trigonometry problems using the Newman error analysis procedure. This research is descriptive qualitative with the subjects of vocational high school students. Data collection involved written tests, depth interviews, and documentation. The results show that most students made comprehension and transformation errors. The comprehension errors consisted of not writing down what was known and asked; immediately writing down the completion process with the wrong formula and incorrect understanding of the concept of the basic trigonometric formula. The transformation errors were not being able to transform information on the problem into the mathematical model, and incorrect in mentioning the formula.